Electrocardiographic Characterization of Ramucirumab on the Corrected QT Interval in a Phase II Study of Patients With Advanced Solid Tumors. (16th March 2016) - Olszanski, Anthony J.; Smith, David C.; Camacho, Luis H.; Thompson, John; Ramalingam, Suresh S.; Harvey, R. Donald; Campos, Luis; Ferry, David; Tang, Shande; Gao, Ling; Safran, Howard
Abstract: Lessons Learned: Cardiotoxicity can be a serious complication of anticancer therapies. To enable earlier identification of drug-related cardiac effects, the International Conference on Harmonization (ICH) adopted the ICH E14 Guidelines for evaluating the potential for QT/corrected QT (QTc) interval prolongation and proarrhythmic potential for nonantiarrhythmic drugs. The results of the evaluation of ramucirumab on the QT/QTc interval show a lack of effect on QTc prolongation in patients with advanced cancer. Background: Ramucirumab is a human immunoglobulin G1 monoclonal antibody that specifically blocks vascular endothelial growth factor receptor-2 and is approved for the treatment of advanced gastric, non-small cell lung, and colorectal cancers. This phase II study was conducted to determine if treatment with ramucirumab causes prolongation of the corrected QT interval using Fridericia's formula (QTcF) in patients with advanced cancer. Methods: Patients received intravenous ramucirumab (10 mg/kg) every 21 days for 3 cycles. The first 16 patients received moxifloxacin (400 mg orally), an antibiotic associated with mild QT prolongation as a positive control. During cycle 3, determination of QTcF prolongation was made with triplicate electrocardiograms at multiple time points to compare with baseline. Results: Sixty-six patients received therapy; 51 patients completed 9 or more weeks of therapy for the complete QTcF evaluation period. The upper limit of the 90% two-sided confidence intervals for the least square means of change in QTcF from baseline at each time point was less than 10 milliseconds. Concentration-QTcF analysis showed a visible, but not significant, negative association between ramucirumab concentration and QTcF change from baseline. Conclusion: Ramucirumab at a dose of 10 mg/kg administered every 21 days for 3 cycles did not produce a statistically or clinically significant prolongation of QTcF.